Variations on the Themes of Netochka Nezvanova - Beržaitė, Dagnė (Literatūra, 2024)
The author of the article examines Fyodor Dostoevsky’s first multi-plot novel Netochka Nezvanova while also exploring the versions and reasons for the novel’s incompletion. The article suggests reading it in the context of the autobiographical works of Anna Grigorievna Dostoevskaya. The article draws a parallel between the first part of the novel about the musician Efimov and fragments from the Diaries and Memoirs of the writer’s wife. For the contemporary reader, accustomed to reading differently constructed texts, these fragments might be perceived as a kind of sequel to the early unfinished work (for example, the names of the novel’s heroine and the writer’s second wife, certain dates, behavioral models, and similar situations). The article suggests the idea that incorporating a literary text into the context of a writer’s biography is one way of ‘completing the incomplete’, while at the same time expanding the possibilities of interpreting classic works.
Keywords: Dostoevsky; Netochka Nezvanova; unfinished novel; Dostoevskaya; reader; sequel